Analisis Keseimbangan Ranah Kognitif, Afektif dan Psikomotorik dalam Muatan Ekologi pada Kurikulum Pendidikan Agama Kristen Sekolah Menengah Atas - Andrias Pujiono (REAL DIDACHE: Journal of Christian Education, 2022)
Knowledge of what environmental care is does not automatically make a person care for the environment in his actions. For this reason, it is necessary to have an education that is holistic, that is, that touches on cognitive, affective, and psychomotor aspects. With a holistic approach learner are not only able to understand but also behave and act positively towards the environment in which they live. In the context and practice of Christian religious education, it is necessary to have holistic ecological education as stated in the ecological content. To find out this, the author analyzes the ecological content in the high school Christian religious education curriculum, in order to find out the balance of its domains. From this analysis, it is proven that the ecological content in the curriculum of Christian religious education at the high school level tends to be cognitive and not holistic.Keywords: affective; ecological; balance; cognitive; psychomotorAbstrakPengetahuan tentang apa itu peduli lingkungan tidak otomatis menjadikan seseorang peduli lingkungan dalam tindakannya. Untuk itu, perlu pendidikan yang bersifat holistik, yaitu yang menyentuh aspek kognitif, afektif, dan psikomotorik. Dengan pendekatan yang holitik peserta didik tidak hanya mampu memahami tetapi juga bersikap dan bertindak positif terhadap lingkungan di mana mereka tinggal. Dalam konteks dan praktik pendidikan agama Kristen perlu adanya pendidikan ekologi holistik yang tertuang dalam muatan ekologi. Untuk mengetahui hal tersebut, penulis melakukan analisa terhadap muatan ekologi pada kurikulum pendidikan agama Kristen sekolah menengah atas, guna mengetahui keseimbagan ranah-ranahnya. Dari analisa tersebut, terbukti muatan ekologi dalam kurikulum pendidikan agama Kristen tingkat sekolah menengah atas cenderung bersifat kognitif dan tidak bersifat holistik.Kata kunci: afektif; ekologi; keseimbangan; kognitif; psikomotor